Expression Profile and Prognostic Values of HOXA Family Members in Laryngeal Squamous Cell Cancer - Li, Jinyun; Ye, Meng; Zhou, Chongchang (Frontiers in Oncology, 2020)
The homeobox A cluster (HOXA) gene family, comprising 11 members, is involved in a wide spectrum of biological functions in human cancers. However, there is little research on the expression profile and prognostic values of HOXA genes in laryngeal squamous cell cancer (LSCC). Based on updated public resources and integrative bioinformatics analysis, we assessed the expression profile and prognostic values of the HOXA family members. Expression and methylation data on HOXA family members were obtained from The Cancer Genome Atlas (TCGA). The prognostic values of HOXA members and clinical features were identified. A gene set enrichment analysis (GSEA) was conducted to explore the mechanism underlying the involvement of HOXA members in LSCC. The associations between tumor immune infiltrating cells (TIICs) and the HOXA family members were evaluated using the Tumor Immune Estimation Resource (TIMER) database. HOXA2 and HOXA4 were downregulated and HOXA7 and HOXA9–13 were upregulated in LSCC. Upregulation of HOXA10, HOXA11 and HOXA13, along with two clinical characteristics (M stage and gender), were associated with a poor LSCC prognosis based on the results of univariate and multivariate Cox proportional hazards regression analyses. Although there were no significant correlations between TIICs and HOXA members, the GSEA results indicated that HOXA members participate in multiple biological processes underlying tumorigenesis. This study comprehensively analyzed the HOXA members, providing insights for further investigation of the HOXA family members as potential targets in LSCC.